In vivo selection for Haemonchus contortus resistance to monepantel - Niciura, S. C.M. (2020)
Gastrointestinal nematodes significantly affect the ovine industry, and Haemonchus contortus is considered the most pathogenic parasite in tropical regions. This situation is aggravated when the main strategy to control worms fails because of the genetic resistance that parasites acquire against anthelmintics. Aiming to anticipate the events involved in anthelmintic resistance, we induced monepantel resistance in H. Contortus by in vivo subdosing of sheep hosts. Four successive passages of a monepantel-susceptible H. Contortus isolate in Santa Ines or Ile de France sheep hosts resulted in three monepantel-resistant (efficacy varying from 0 to 58.5%) H. Contortus isolates. Sheep hosts were treated from 0.075 mg/kg to the therapeutic dose of 2.5 mg/kg of monepantel in 19-26 rounds of selection for 112-133 weeks. Success in inducing H. Contortus resistance to monepantel may have been affected by worm burden and by host-parasite interactions, including a possible effect of the breed of sheep hosts. We conclude that subdosing of sheep, although time-consuming, is an efficient in vivo strategy for the induction of monepantel resistance in H. Contortus. The resistant parasites can be used in further studies to elucidate the genetic and biochemical events involved in the acquisition of anthelmintic resistance.